Evaluating partisan gains from Congressional gerrymandering: Using computer simulations to estimate the effect of gerrymandering in the U.S. House. (December 2016) - Chen, Jowei; Cottrell, David
Abstract: What is the effect of gerrymandering on the partisan outcomes of United States Congressional elections? A major challenge to answering this question is in determining the outcomes that would have resulted in the absence of gerrymandering. Since we only observe Congressional elections where the districts have potentially been gerrymandered, we lack a non-gerrymandered counterfactual that would allow us to isolate its true effect. To overcome this challenge, we conduct computer simulations of the districting process to redraw the boundaries of Congressional districts without partisan intent. By estimating the outcomes of these non-gerrymandered districts, we are able to establish the non-gerrymandered counterfactual against which the actual outcomes can be compared. The analysis reveals that while Republican and Democratic gerrymandering affects the partisan outcomes of Congressional elections in some states, the net effect across the states is modest, creating no more than one new Republican seat in Congress. Therefore, the partisan composition of Congress can mostly be explained by non-partisan districting, suggesting that much of the electoral bias in Congressional elections is caused by factors other than partisan intent in the districting process. Highlights: Computer simulations distinguish partisan gerrymandering and natural electoral bias. Most electoral bias results from the geographic concentration of partisan voters. Partisan gerrymandering produces more Republican districts in Republican-controlled states and more Democratic districts in Democrat-controlled states. But nationally, the net effect of gerrymandering on the partisan control of Congressional seats is modest.